Effect of the Arc Welding Parameters on the Built-Up Layer by EFeCr-A1 Electrode on Austenitic Stainless Steel - Vu, Dinh Toai (Old Journal, 2019)
Hardfacing of the details by austenitic stainless steel in chemical plants is a useful solution to increase the working life of details and reduces the operating costs of the equipment. This paper investigates the effect of the SMAW welding parameters (heat input) on the quality of the built-up layer by EFeCr-A1 welding electrode on SUS304 stainless steel, through which the suitable welding parameter is selected. Research has shown that when welding the EFeCr-A1 welding electrode with a diameter of φ=3.2mm, the suitable heat input is q=1056.52 J/mm. With these parameters, the hardness of the carbide phase in the weld metal is 672 HV (equivalent to 59 HRC). If welding with a heat input of q≤940.97 J/mm, the weld bead will not be formed, and if welding with a heat input of q ≥ 1207.50 J/mm then the base metal will dissolve too much into the built-up layers, therefore the hardness of the hard surface layer is not high.